2021
DOI: 10.1186/s12870-021-02954-2
|View full text |Cite
|
Sign up to set email alerts
|

Cold acclimation can specifically inhibit chlorophyll biosynthesis in young leaves of Pakchoi

Abstract: Background Leaf color is an important trait in breeding of leafy vegetables. Y-05, a pakchoi (Brassica rapa ssp. chinensis) cultivar, displays yellow inner (YIN) and green outer leaves (GOU) after cold acclimation. However, the mechanism of this special phenotype remains elusive. Results We assumed that the yellow leaf phenotype of Y-05 maybe caused by low chlorophyll content. Pigments measurements and transmission electron microscopy (TEM) analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 71 publications
1
5
0
Order By: Relevance
“…Chlorophyll is an essential cofactor for photosynthesis, and maintaining a normal chlorophyll state and level is essential for photosynthetic efficiency and carbon fixation, which directly influence plant growth and development under various abiotic stresses [ 18 ]. Comparing seedlings of 39 maize genotypes exposed to 10 °C low-temperature stress with 22 °C control, 10 °C significantly reduced the contents of Chl a, Chl b, Chl a+b in their leaves by 18.6%, 21.7%, and 20.3%, respectively; however, chlorophyll a:b ratio (Chl a/b) slightly increased by 3.3% ( Figure 1 and Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Chlorophyll is an essential cofactor for photosynthesis, and maintaining a normal chlorophyll state and level is essential for photosynthetic efficiency and carbon fixation, which directly influence plant growth and development under various abiotic stresses [ 18 ]. Comparing seedlings of 39 maize genotypes exposed to 10 °C low-temperature stress with 22 °C control, 10 °C significantly reduced the contents of Chl a, Chl b, Chl a+b in their leaves by 18.6%, 21.7%, and 20.3%, respectively; however, chlorophyll a:b ratio (Chl a/b) slightly increased by 3.3% ( Figure 1 and Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…In this study, the expression of CfCHLM in C. fortunei was shown to be downregulated under abiotic stress, and the downregulation of the CHLM gene may have inhibited the synthesis of chl. Many studies have shown that the synthesis of chl is inhibited under various abiotic stresses [28][29][30][31], which demonstrates the downregulation of the CfCHLM gene in response to stress.…”
Section: Functional Analysis and Expression Pattern Of Cfchlmmentioning
confidence: 99%
“…In an important study on the mechanism of stress response, Wang et al (2021) identified the fluorescence in blue light (BrFLU) gene in Pak Choi; the gene was shown to be related to cold acclimation in a study that combined transcriptomics methods.…”
Section: Application Of Metabolomics To Plant Breedingmentioning
confidence: 99%